Effect of social play deprivation on stress sensitivity in response to social and non-social challenges - Achterberg, E. J. Marijke; Lozeman-van ‘t Klooster, Jose G.; Pimentel, Tara C.; Aleksić, Anastasija; Hendriks, Judith C. M. J.; Nijhof, Sanne; van der Ent, C. Kors; Lesscher, Heidi M. B. (Frontiers in Ethology, 2024)
IntroductionSocial play behaviour facilitates the development of social, emotional and cognitive capacities, including resilience. Deprivation of social play in rats leads to alterations in anxiety, stress and social behaviour. The aim of this study was to elucidate the effects of social play deprivation, specifically on the responsivity to social and non-social challenges. We hypothesised that play deprivation leads to impairments in stress resilience later in life, particularly in social contexts. MethodsTo test this, play-deprived rats were compared with undeprived control rats for their responsivity to (1) a novel environment, (2) facing an aggressive male rat in its territory (resident-intruder test) and (3) an encounter with two unfamiliar conspecifics in a neutral, familiar environment (stranger encounter test). ResultsCorticosterone concentrations in response to these different stressors were comparable between play-deprived and control rats. Behavioural analysis revealed that play-deprived rats responded similar to undeprived controls when confronted with an aggressive rat in its territory. In the stranger encounter test, the unfamiliar strangers directed more play behaviour towards play-deprived animals than towards undeprived control animals. DiscussionTogether our results indicate that, except for subtle differences in play behaviour in a social challenging condition, play deprivation did not result in altered corticosterone responses to the different stressors. Our data add to the existing knowledge about the impact of social play for the development of resilient and social behaviour later in life.